Качественная парадигма в библиотековедческих исследованиях (Библиосфера, 2011)
Problems associated with the methodology of conducting qualitative research in library science. Philosophical questions of qualitative research, peculiarities of developing a scientific program of projects implemented in the form of qualitative paradigm are accented. Much attention is paid to the essential differences of qualitative and quantitative researches their limitations and advantages.